2014
DOI: 10.1111/ggi.12345
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self‐rated oral health among community‐dwelling older Japanese: A cross‐sectional study

Abstract: The present results suggested that self-rated oral health was a significant factor in oral health status as well as overall well-being among community-dwelling older Japanese people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 44 publications
3
17
1
4
Order By: Relevance
“…Bandura expressed that individuals have outcome expectations when they act, meaning that certain desirable outcomes are expected as a result of taking action. 8 Self-rated oral health is one of the key outcomes reflected by one's oral condition as well as social well-being, 20 and the present study suggested that positive acceptance of oral health was associated with a higher level of oral health-related self-efficacy.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Bandura expressed that individuals have outcome expectations when they act, meaning that certain desirable outcomes are expected as a result of taking action. 8 Self-rated oral health is one of the key outcomes reflected by one's oral condition as well as social well-being, 20 and the present study suggested that positive acceptance of oral health was associated with a higher level of oral health-related self-efficacy.…”
Section: Discussionsupporting
confidence: 51%
“…Self‐rated oral health was assessed with the question "What do you think of your oral health?" (response options: good, rather good, rather poor and poor) …”
Section: Methodsmentioning
confidence: 99%
“…These comprise low education and/or low income (Guarnizo-Herreno et al, 2014;Sanders & Spencer, 2005;Trachte, Geyer, & Sperlich, 2016;Turrell, Sanders, Slade, Spencer, & Marcenes, 2007), smoking (Csikar et al, 2016), frequent stress events, or obesity (Lee, Song, Yang, & Kang, 2015). Also, overt symptoms of oral disease contribute to poor rating, such as the number of lacking teeth, difficulty in mastication, or xerostomia (Ohara et al, 2015). Moreover, the frequency of dental attendance seems to be a factor (Northridge et al, 2012).…”
Section: Ta B L E 1 Comparison Of Baseline Figures Of Interest Betweementioning
confidence: 99%
“…One reason to explain why adults aged 65 years and older had lower odds of reporting poor oral health than younger age groups is that factors influencing self-perceived oral health status may differ along the life course. [19][20][21][22] In addition, comparisons to age, peers and social norms, such as the social ideal of straight white teeth in North American culture, 23 may also influence perceptions of oral health. 19 The extent to which various social and clinical factors influence these self-reports are beyond the scope of this analysis but have been explored elsewhere in the literature.…”
Section: Contributions To Oral Health Inequalitiesmentioning
confidence: 99%
“…19 The extent to which various social and clinical factors influence these self-reports are beyond the scope of this analysis but have been explored elsewhere in the literature. [20][21][22]24 Utilizing chewing difficulties as an additional measure arguably enables an understanding of how respondents describe their oral health in terms of symptoms and function. This measure can be considered as a proxy indicator of oral disease burden, as chewing difficulties likely inhibit normal functioning and may be the result of oral disease (periodontal disease, caries); this may ultimately be the consequence of an inability to receive timely preventive or curative care.…”
Section: Contributions To Oral Health Inequalitiesmentioning
confidence: 99%